2019
DOI: 10.1126/sciadv.aav7689
|View full text |Cite
|
Sign up to set email alerts
|

A light-driven burst of hydroxyl radicals dominates oxidation chemistry in newly activated cloud droplets

Abstract: Aerosol particles and their interactions with clouds are one of the most uncertain aspects of the climate system. Aerosol processing by clouds contributes to this uncertainty, altering size distributions, chemical composition, and radiative properties. Many changes are limited by the availability of hydroxyl radicals in the droplets. We suggest an unrecognized potentially substantial source of OH formation in cloud droplets. During the first few minutes following cloud droplet formation, the material in aeroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(107 citation statements)
references
References 85 publications
11
94
2
Order By: Relevance
“…redox state, solubility, speciation) of Fe, to the variability of emission sources of Fe between the seasons, or to some other important additional contribution to ROS in the summer; complexation of the Fe may differ between seasons, and the ligands can directly influence the redox state and bioavailability of the metal (Ghio et al, 1999). Interestingly, a mild inverse correlation of Fe with DCFHm is observed ( Table S8, not statistically significant), which may be linked to the destruction of particle-bound organic peroxides by Fe via Fenton-type chemistry (Charrier et al, 2014), a process which the DCFH assay is specifically sensitive to (Gallimore et al, 2017;Wragg et al, 2016), and which has been observed in other recent studies (Paulson et al, 2019). No significant positive correlation between any metals measured in this study and DCFHm and EPRm was observed.…”
Section: Univariate Analysis Of Pm Opm and Additional Measurementssupporting
confidence: 58%
“…redox state, solubility, speciation) of Fe, to the variability of emission sources of Fe between the seasons, or to some other important additional contribution to ROS in the summer; complexation of the Fe may differ between seasons, and the ligands can directly influence the redox state and bioavailability of the metal (Ghio et al, 1999). Interestingly, a mild inverse correlation of Fe with DCFHm is observed ( Table S8, not statistically significant), which may be linked to the destruction of particle-bound organic peroxides by Fe via Fenton-type chemistry (Charrier et al, 2014), a process which the DCFH assay is specifically sensitive to (Gallimore et al, 2017;Wragg et al, 2016), and which has been observed in other recent studies (Paulson et al, 2019). No significant positive correlation between any metals measured in this study and DCFHm and EPRm was observed.…”
Section: Univariate Analysis Of Pm Opm and Additional Measurementssupporting
confidence: 58%
“…Given the rate constants (Table 1 ), OH ⋅ , HO 2 ⋅ /O 2 ⋅ − need to be ~ 10 –9 , 10 –4 × [Fe(III)] or 10 –8 , 10 –3 × [Cu(II)], respectively to account for around half of ascorbate loss. OH ⋅ , HO 2 ⋅ in liquid phases in equilibrium with gas phase concentrations of 10 6 and 10 7 molec/cm 3 result in liquid phase concentrations of ~ 10 –3 and 10 –2 nM, respectively 48 . However, even with modest concentrations of organics, the radicals will be rapidly depleted away from the interface 48 .…”
Section: Resultsmentioning
confidence: 99%
“…A simplified reaction scheme that involves a sequential reaction of phenol (aq) with OH (aq) and NO 2(aq) is incorporated into the model (Barzaghi & Herrmann, 2002, 2004; Harrison, Heal, et al, 2005). In the scheme, OH radicals in the aerosol water are either generated with a daytime production rate of (0.3–3) × 10 −10 M s −1 (Arakaki & Faust, 1998; Bianco et al, 2015; Wang et al, 2012; Zhang et al, 2009) or remain constant in the range of 0.1–3.5 μM, a substantially high level that is likely present in nascent cloud droplets (Paulson et al, 2019). As shown in Figure 3d, increasing aqueous OH concentrations does not necessarily enhance the production of nitrophenols as the dissolved NO 2(aq) generated from the photolysis of nitrate and uptake of gas phase NO 2 can be rapidly consumed by hydrolysis and reaction with OH (aq) (see detailed reactions listed in Table S2 in the supporting information).…”
Section: Resultsmentioning
confidence: 99%